Understanding and studying the effects of termination of analogue television system toward Roi-et’s consumers - สิริวัฒนตระการ, เชษฐพัฒน์ (Journal of Humanities and Social Sciences, Rajapruk University, 2016)
This research aims 1) To explore the digital TV in Roi Et province 2) To study awareness of the people about the digital TV transition to digital TV. in Roi Et province. 3) To study satisfaction of the people who watch digital TV. in Roi Et province. The researchers collected data from 65,000 sample people in the analysis of quantitative data. Statistical software was used for finding frequency, percentage, average, and standard deviation. Overall, 49,023 or 75.42 % of people in Roi Et currently watch TV via satellite, 7,730 people or 11.89% of antenna and 7,171people or 11.04% of cable TV as fallow. As Roi Et people, 35 298 or 54.30 percent of people known and can turn on and off the digital TV, 20,713 or 31.87 percent of people is an unknown digital TV and 13,567 people or 20.87 percent of people know and know how to adjust the station. The number of people who watch digital TV via satellite is 39,252 or 60.39 percent, 20,681 or 31.82 percent of people used old television and of and Digital 13,449 or 20.69 percent of people used TV HD (high definition). In addition, 43,144 or 66.38 percent of people want to convert to antenna receiver for digital TV and 21, 856 or 33.62 percent of people will not change.